ISLAM'S VIEW ON CHANGES IN FASHION TRENDS IN INDONESIA - Silaturrohmah, Firda; Masruroh, Nikmatul; Dzulkarnaen, Ahmad (Pascasarjana UIN Kiai Haji Achmad Siddiq Jember, 2024)
One of the interesting phenomena of social change to discuss is the matter of clothing style (fashion trends). Initially, Indonesian people only wore Islamic clothing at certain moments, such as events related to religion. However, today society tends to prioritize material interests above all else, even above religion. Transformation in society is often based on dissatisfaction with certain aspects of life. One of the transformations that occurs and is very visible is the evolution of changes in clothing fashion. This is in line with the rapid development of technology which is followed by several developments, including in this case the development of clothing styles. We cannot avoid this development, aligning an existing development is a necessity that needs to be done, but even so there are sharia rules that have been finalized and must be obeyed by Muslims in full. There have been various fatwas issued by scholars, but it seems that these fatwas are often ignored.